Peran Kepala Sekolah Sebagai Supervisor Kinerja Guru Bimbingan dan Konseling - Muhammad Eka Prasetia (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to determine the description of the role of the principal as a supervisor in improving the performance of Guidance and Counseling Teachers at SMA Negeri 10 Banjarmasin City. The approach in this study uses a qualitative approach with a phenomenological research design. The method used in this study in collecting data is to use interview and documentation techniques, which will then be analyzed and seen for the validity of the data using data triangulation techniques. The results obtained based on data collected through interviews and documentation found that the Principal of SMA Negeri 10 Banjarmasin has carried out his roles and functions as well as duties and responsibilities as school supervisors by carrying out planned and scheduled supervision of guidance and counseling teachers in improving their performance. In addition, based on the data collected through interviews and documentation, it is known that the supervision technique used by the Principal of SMA Negeri 10 Banjarmasin is an individual technique using 3 supervision activities, namely, class visits, class observations and individual interviews.